Leptospiróza po povodních - Zadrobílková, Eliška; Kodym, Petr (Zprávy Centra epidemiologie a mikrobiologie, 2024)
x
Keywords: zoonózy; leptospiróza; lidé; Leptospirosis; Humans; Leptospira; záplavy; Zoonoses; Floods